ANALISIS KERUSAKAN STRUKTUR BANGUNAN GEDUNG BAPPEDA WONOGIRI - Hartono, Henry (Dinamika Teknik Sipil, 2007)
The BAPPEDA office building of Wonogiri regency is an office owned by The Government of Wonogiri Regency that has a function as a Development Planning Board and Research Office of the Regional Development in Wonogiri regency. The building was built in 199